Effect of glucose oxidase incorporation in chitosan edible films properties - Lopes, M. I. (2011)
Demand for biodegradable and environmentally friendly packaging has draw attention into the development of biodegradable, polymer based edible packaging films. Edible films’ functionality can be enhanced by incorporating active substances such as biocatalysts. The main objective of this work was to evaluate the effect of GOx incorporation in the mechanical and barrier properties of chitosan edible films. Films were prepared by the casting method using 2% (w/v) chitosan with 25% (w/w) glycerol, containing 1.1% (v/v) of a glucose oxidase solution (0.02% (w/v)). Water vapor, oxygen and carbon dioxide permeabilities were evaluated and Fourier Transform InfraRed (FTIR) analysis was performed. The results of the mechanical tests showed that tensile strength and elongation-at-break values of chitosan films increased with the incorporation of glucose oxidase (from 9.6 to 10.6 MPa and from 65.5 to 71.6 %, respectively), however no significant (p<0.05) changes were observed. From permeability tests it was observed that the barrier properties of chitosan films were not affected by the enzyme incorporation. FTIR analysis showed a specific chemical interaction between functional groups of glucose oxidase and bioactive groups of chitosan. These results suggest that chitosan films with incorporated GOx could be used as active packaging as a strategy for extension of food’s shelf-life.